Reducing free fatty acid and peroxide levels in refining used cooking oil made from activated carbon from Barangan banana peels - Dian Frasisca; Ety Jumiati; Masthura Masthura (Universitas Riau, 2024)
Everyday life requires a food processing component known as cooking oil. Repeated use of cooking oil can reduce its quality and cause it to have high levels of free fatty acids and peroxides. The purpose of this study was to find out how to purify cooking oil using activated carbon made from Barangan banana peels to reduce the amount of free fatty acids and peroxide value. The activated carbon samples used in this study were sample A (5.5 g), sample B (10.5 g), and sample C (15.5 g). Sample C with 15.5 g of activated carbon had a free fatty acid test result of 0.16% and a peroxide number of 3.91 mek O2/kg which was the best result in this study, and was in accordance with SNI 01-7709-2019.